Challenges Faced by Prehospital Emergency Physicians Providing Emergency Care to Patients with Advanced Incurable Diseases - Anne Kamphausen; Hanna Roese; Karin Oechsle; Malte Issleib; Christian Zöllner; Carsten Bokemeyer; Anneke Ullrich (Emergency Medicine International)
Introduction. The aim of our study was to investigate challenges faced by emergency physicians (EPs) who provide prehospital emergency care to patients with advanced incurable diseases and family caregivers in their familiar home environment. Methods. Qualitative study using semistructured interviews with open-ended questions to collect data from 24 EPs. Data were analyzed using qualitative content analysis. Results. We identified nine categories of challenges: structural conditions of prehospital emergency care, medical documentation and orders, finding optimal patient-centered therapy, uncertainty about legal consequences, challenges at the individual (EP) level, challenges at the emergency team level, family caregiver’s emotions, coping and understanding of patient’s illness, patient’s wishes, coping and understanding of patient’s illness, and social, cultural, and religious background of patients and families. EPs strengthened that the integrations of specialized prehospital palliative care services improved emergency care by providing resources to patients and family caregivers, enhancing the quality and availability of medical documentation and accessibility of aftercare in emergencies. Areas of improvement that were identified were to promote emergency physicians’ knowledge and skills in palliative care, communication, and family caregiver support by education and training. Furthermore, structures for better care on-site, thorough medical documentation, and specialized palliative care emergency facilities in hospital and prehospital care were requested. Conclusion. Prehospital emergency care in patients with advanced incurable diseases in their familiar home environment may be improved by training EPs in palliative care, communication, and caregiver support competences. Results underline the importance of collaborative specialized palliative care and prehospital emergency care.